Analysis of Coastal Abrasion Rate of Laha Village Ambon City using Satellite Data - Samallo, Zulfikri; Warniyati, Warniyati; Sihombing, Tri Octaviani; Tutkey, Monica R (Institut Teknologi Adhi Tama Surabaya, 2024)
The coastline is the boundary between the sea and land. Line changes are caused by abrasion and accretion. Abrasion and accretion occur throughout the coast of Laha so that the coastline undergoes quite drastic changes. This study aims to determine how much the average rate of abrasion and coastal accretion per year and how much the average area of abrasion and accretion for 10 years of recording data on the Laha coast. This study uses the remote sensing method as a rapid study to detect the rate of abrasion and accretion on Laha beach using Landsat 8 images in 2013, 2014, 2015, 2016, 2017, 2018, 2019, 2020, 2021, 2022 as primary data Calculation of shoreline changes using DSAS (digital shoreline analysis system) using the NSM (net shoreline movement) statistical method. The results of the 10-year coastal abrasion rate study occurred thoroughly on the coast of Laha beach. The highest abrasion occurred in 2018-2019 with an average value of NSM -15 cm/year while the highest accretion occurred in 2019-2020 with an average value of NSM +19.97 cm/year. Abrasion area for 10 years with an average value of NSM of -89.29 m2 / year while accretion for 10 years with an average value of NSM of +70.70 m2/ year. With the rate of abrasion that occurs, it is necessary to build coastal buildings evenly so that abrasion can be minimized.